Double‐hydrophobic elastin‐like polypeptides with added functional motifs: Self‐assembly and cytocompatibility. Issue 9 (6th June 2017) - Le, Duc H. T.; Tsutsui, Yoko; Sugawara‐Narutaki, Ayae; Yukawa, Hiroshi; Baba, Yoshinobu; Ohtsuki, Chikara
Abstract: We have recently developed a novel double‐hydrophobic elastin‐like triblock polypeptide calledGPG, designed after the uneven distribution of two different hydrophobic domains found in elastin, an extracellular matrix protein providing elasticity and resilience to tissues. Upon temperature trigger, GPG undergoes a sequential self‐assembling process to form flexible beaded nanofibers with high homogeneity and excellent dispersibility in water. Given thatGPG might be a potential elastin‐mimetic material, we sought to explore the biological activities of this block polypeptide. BesidesGPG, several functionalized derivatives were also constructed by fusing functional motifs such as KAAK or KAAKGRGDS at the C‐terminal ofGPG . Although the added motifs affected the kinetics of fiber formation and β‐sheet contents, all threeGPG s assembled into beaded nanofibers at the physiological temperature. The resultingGPG nanofibers preserved their beaded structures in cell culture medium; therefore, they were coated on polystyrene substrates to study their cytocompatibility toward mouse embryonic fibroblasts, NIH‐3T3. Among the three polypeptides, GPG having the cell‐binding motif GRGDS derived from fibronectin showed excellent cell adhesion and cell proliferation properties compared to other conventional materials, suggesting its promising applications as extracellular matrices for mammalian cells. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2475–2484, 2017.